Preparation of a weak anion exchange/hydrophobic interaction dual‐function mixed‐mode chromatography stationary phase for protein separation using click chemistry. Issue 5 (27th January 2015) - Zhao, Kailou; Yang, Fan; Xia, Hongjun; Wang, Fei; Song, Qingguo; Bai, Quan
<x xml:space="preserve">Abstract</x> In this study, 3‐diethylamino‐1‐propyne was covalently bonded to the azide‐silica by a click reaction to obtain a novel dual‐function mixed‐mode chromatography stationary phase for protein separation with a ligand containing tertiary amine and two ethyl groups capable of electrostatic and hydrophobic interaction functionalities, which can display hydrophobic interaction chromatography character in a high‐salt‐concentration mobile phase and weak anion exchange character in a low‐salt‐concentration mobile phase employed for protein separation. As a result, it can be employed to separate proteins with weak anion exchange and hydrophobic interaction modes, respectively. The resolution and selectivity of the stationary phase were evaluated in both hydrophobic interaction and ion exchange modes with standard proteins, respectively, which can be comparable to that of conventional weak anion exchange and hydrophobic interaction chromatography columns. Therefore, the synthesized weak anion exchange/hydrophobic interaction dual‐function mixed‐mode chromatography column can be used to replace two corresponding conventional weak anion exchange and hydrophobic interaction chromatography columns to separate proteins. Based on this mixed‐mode chromatography stationary phase, a new off‐line two‐dimensional liquid chromatography technology using only a single dual‐function mixed‐mode chromatography column was developed. Nine kinds of tested proteins can be separated completely using the developed method within 2.0 h.